Accelerated 3D T2w‐imaging of the prostate with 1‐millimeter isotropic resolution in less than 3 minutes. Issue 2 (21st April 2019) - Vidya Shankar, Rohini; Roccia, Elisa; Cruz, Gastao; Neji, Radhouene; Botnar, René; Prezzi, Davide; Goh, Vicky; Prieto, Claudia; Dregely, Isabel
Abstract : Purpose: To achieve 3D T2 w imaging of the prostate with 1‐mm isotropic resolution in less than 3 min. Methods: We devised and implemented a 3D T2 ‐prepared multishot balanced steady state free precession (T2 prep‐bSSFP) acquisition sequence with a variable density undersampled trajectory combined with a total variation regularized iterative SENSE (TV‐SENSE) reconstruction. Prospectively undersampled images of the prostate (acceleration factor R = 3) were acquired in 11 healthy subjects in an institutional review board‐approved study. Image quality metrics (subjective signal‐to‐noise ratio, contrast, sharpness, and overall prostate image quality) were evaluated by 2 radiologists. Scores of the proposed accelerated sequence were compared using the Wilcoxon signed‐rank and Kruskal‐Wallis non‐parametric tests to prostate images acquired using a fully sampled 3D T2 prep‐bSSFP acquisition, and with clinical standard 2D and 3D turbo spin echo (TSE) T2 w acquisitions. A P ‐value < 0.05 was considered significant. Results: The 3× accelerated 3D T2 prep‐bSSFP images required a scan time (min:s) of 2:45, while the fully sampled 3D T2 prep‐bSSFP and clinical standard 3D TSE images were acquired in 8:23 and 7:29, respectively. Image quality scores (contrast, sharpness, and overall prostate image quality) of the accelerated 3D T2 prep‐bSSFP, fully sampled T2 prep‐bSSFP, and clinical standard 3D TSE acquisitions along all 3 spatial dimensions were not significantly different ( P > 0.05). Conclusion: 3D T2 w images of the prostate with 1‐mm isotropic resolution can be acquired in less than 3 min, with image quality that is comparable to a clinical standard 3D TSE sequence but only takes a third of the acquisition time.